AN ANALYSIS OF STUDENTS’ ENGLISH VOCABULARY MASTERY AND TRANSLATION ABILITY IN SENIOR HIGH SCHOOL - Hariyanto, Hariyanto; Wulandari, Fariska (LPPM IKIP PGRI Pontianak, 2019)
Abstract Learning language especially English as the foreign language is crucial. People who want to learn English have to at least possess English vocabulary mastery and translation ability. The purposes of this research are to find out students capability in English vocabulary mastery and translation ability andto find out the problems that students face in learning English. The research was conducted on XI grade students. In this research, the writer used interview, observation, vocabulary mastery test, translation ability test and literature study to obtain the data. Based on the findings of this research, it can be concluded that the average score of students’ vocabulary mastery test is 65.15 and the average score of students’ translation ability is 63.93. Both indicate that students capability in English language especially in vocabulary mastery and translation ability is low. Students also faced difficulties in answering questions containing low frequency vocabularies because they rarely see or read the words. AbstrakBelajar bahasa Inggris merupakan hal yang sangat penting. Orang yang ingin belajar bahasa paling tidak harus memiliki kemampuan kosakata dan menerjemah. Tujuan penelitian adalah untuk mengetahui kemampuan kosakata dan menerjemah siswa dan mengetahui masalah yang dihadapi oleh para siswa dalam belajar bahasa Inggris. Penelitian dilaksanakan di kelas XI MIPA SMA Santo Fransiskus Asisi Pontianak. Penulis menggunakan wawancara, observasi, tes kemampuan kosakata, tes kemampuan menerjemah dan studi literatur untuk mengumpulkan data. Berdasarkan temuan penelitian, dapat disimpulkan bahwa nilai rata-rata tes kemampuan kosakata siswa adalah 65,15 dan nilai rata-rata kemampuan menerjemah siswa adalah 63,93. Keduanya mengindikasikan bahwa kemampuan kosakata dan menerjemah siswa berada pada kategori rendah. Temuan penelitian juga menunjukkan bahwa para siswa kesulitan dalam menjawab pertanyaan yang berisikan kosakata dengan frekuensi rendah karena jarang melihat atau membaca kosakata tersebut.